Conservation, acquisition, and functional impact of sex-biased gene expression in mammals - Naqvi, Sahin; Godfrey, Alexander K.; Hughes, Jennifer F.; Goodheart, Mary L.; Mitchell, Richard N.; Page, David C. (Science (American Association for the Advancement of Science), 2019)
In mammals, many species exhibit sex-specific phenotypes that differ between males and females. Although attention has been directed to the effects of the X and Y sex chromosomes, we do not understand how sex affects the rest of the genome. Naqvi et al. examined gene expression in 12 tissues in male and female humans, mice, rats, dogs, and cynomolgus macaques and identified diversity in gene expression between the sexes. Examining sex-biased gene expression in human height identified opposing male or female bias. Although conservation of differential sex-specific gene expression among species was observed, specific genes differed in the sexes among species and lineages suggesting the evolution of species- or lineage-specific sex-biased expression. Science , this issue p. eaaw7317 Mammalian genome-wide gene expression varies between males and females. Sex differences abound in human health and disease, as they do in other mammals used as models. The extent to which sex differences are conserved at the molecular level across species and tissues is unknown. We surveyed sex differences in gene expression in human, macaque, mouse, rat, and dog, across 12 tissues. In each tissue, we identified hundreds of genes with conserved sex-biased expression—findings that, combined with genomic analyses of human height, explain ~12% of the difference in height between females and males. We surmise that conserved sex biases in expression of genes otherwise operating equivalently in females and males contribute to sex differences in traits. However, most sex-biased expression arose during the mammalian radiation, which suggests that careful attention to interspecies divergence is needed when modeling human sex differences.